The Relationship between Learning Implementation and Teacher Self-Efficacy, Job Satisfaction, and Collaboration - Samsudin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
In the 21st century, the importance of effective teaching practices in facilitating student understanding and success, especially in the context of 21st century education. The urgency of this study lies in efforts to improve the quality of teaching in schools, which has the potential to impact student learning outcomes. The purpose of this study was to identify and analyse the relationship between factors and their impact on the implementation of teacher teaching materials. The method used is a quantitative survey type with a sample of 580 teachers from high schools in Jakarta, random sample selection. Data collection techniques are carried out through validated instruments and based on assessments with a Likert scale from point 1 and point 5. Data analysis techniques with SPSS Version 29 and data are analysed with structural equation modeling to understand the relationship between variables. The results of the study indicate that teacher self-efficacy is the main factor contributing to good teaching practices, followed by teacher collaboration and the mediating effect of stress. These findings emphasize the importance of increasing self-efficacy and collaboration among teachers for better teaching practices. In conclusion, interventions that support the development of teacher self-efficacy and collaboration are needed to improve the quality of learning. The implications of this research provide important insights for educational policy and teacher professional development.